Perbandingan Formulasi Dan Uji Stabilitas Fisik Sediaan Gel Ekstrak Lidah Buaya (Aloe Vera) Dengan Perbedaan Konsentrasi - Nur Hasanah; Fenita Purnama Sari Indah; Dede Anggraeni; Nurwulan Adi Ismaya; Lela Kania Rahsa Puji (Edu Masda Journal, 2020)
Aloe vera plant has considerable potential as a raw material for natural medicine. In this aloe vera contains various active substances that can cure various diseases. Aloe vera gel is formulated by mixing the results of aloe vera extract with a suiTabel base. A good gel preparation can be obtained by formulating several types of gelling agents, but the most important thing to note is the selection of Gelling agents. Physical stability tests need to be carried out to ensure the quality, safety and benefits of the gel meet the expected specifications and are sTabel during storage. The purpose of this study is to describe and compare the formulations and physical satellites of aloe vera extract gel preparations with different concentrations of bases on each formulation from various literature. This research uses the literature study research method by collecting various sources of literature from 10 research journals. The results of this review explain that all bases used in each formulation with a predetermined concentration value and with a mixture of other ingredients that have been determined produce good physical stability of each formulation.